If you do it, do it right: The need for a common European supervisory architecture for CCPs - Jan Friedrich; Christian Resch; Matthias Thiemann (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
In the context of Brexit, changes to the regulatory architecture of CCPs that empower the European securities markets regulator are under way to prevent the threat of a regulatory race to the bottom. However, this empowerment currently leaves the national supervision of common European rules within the EU intact. This policy letter argues that supervisory arbitrage is as much a threat within the EU as outside of it, wherefore a common supervision of CCP rules in the EU is called for. The paper traces the origins of the current set-up and criticizes the current regulatory proposal by the EU Commission as too cumbersome while discussing possible ways forward to achieve European supervision. In contrast to the current proposal of the Commission, we call for a unified supervision within ESMA, combined with a European fiscal backstop.
urn:nbn:de:hebis:30:3-466854
Keywords: 330; Central Counterparties; European Supervisory Architecture; Capital Markets Union; regulatory arbitrage; EMIR; supervisory arbitrage